Bis[4-(4-aminophenylsulfanyl)phenyl] ketone - Zhang, Gang (International Union of Crystallography, 2009)
The molecule of the title compound, C(25)H(20)N(2)OS(2), has imposed twofold rotation symmetry. The dihedral angle formed by the two crystallographically independent phenyl rings is 79.23 (7)°. In the crystal packing, the molecules are linked by intermolecular N—H⋯O hydrogen bonds, forming chains running parallel to [102].